HUBUNGAN PENGUASAAN KONSEP FISIKA DAN BIOLOGI DENGAN KONTEKS SIKLUS AIR BERDASARKAN CAPAIAN PENGUASAAN KONSEP DAN KEMAMPUAN MENGIDENTIFIKASI MASALAH DI LAPANGAN - Tirsa Mumek; Christophil Medellu; Djeli Alvi Tulandi (Charm Sains: Jurnal Pendidikan Fisika, 2021)
Utilizing the surrounding environment as source of lessons and relate them with the lessons that studied by the student in school are still rarely done nowadays, which make the students not really understand the relation of context and concept. The purpose of this study is to describe the relation between water cycle context with physics concept and other subject base on the result of concept mastery and the ability to identify the problems in the field. The results showed that the correlation between the physics mastery of phase transition with biology concept of evapotranspiration of 8 students is 0.59, the correlation between observations in field to identify the sewage (solid and liquid) on the river with the sewage treatment technology and water pollution control is 1, and correlation between water cycle concept charts and its components with the students ability to identified water sources in the village, neighbourhood and in other places is 0,89.